Condições de funcionamento de escolas do campo: em busca de indicadores de custo-aluno-qualidade - PEREIRA, Ana Cláudia da Silva (2008)
The study was conducted in 2 (two) schools in the municipality of Bujaru field belonging to the micro-Castanhal mesoregion in the Northeast Paraense. His goal was to identify and analyse the conditions for the functioning of schools of the field, aiming to propose indicators of cost-student-quality for this type of school. The selection of schools is guided by the following criteria: distance from the headquarters of the council; about the size; classification in unidocente or pluridocentes; number of teachers, number of students; levels of education offered and the region in which they are embedded. To obtain information from interviews were conducted with: directors, teachers, parents / community representatives and students. In addition to interviews, and observation forms were used in locus. The axes of analysis taken as guiding questions: the operating conditions of and their main problems and needs and what the subjects say that working and studying in / schools of the field on the indicators needed for a field of quality education? After analysing data, we find that the problems faced by teachers, students, parents and administrators who work in schools of the field are related mainly to operations in classes multisseriadas; lack of furniture, equipment and materials; lack of school transport; precarious conditions of infrastructure and lack of teaching staff. On the issue of quality indicators, the subjects showed the following factors as key to improving the quality of teaching in these schools: appropriate infrastructure, (with securities, libraries, laboratories, equipment and educational materials); contraction of staff (teachers, serventes, merendeiras, watchmen and secretary); qualification and upgrading of teacher; transportation and school lunch. The work presents a range of issues that can compose and explain the possible size and indicators of quality, but are not generalized to a larger pool of schools. Of course, there are regularities, and similar aspects that are common and should be considered for schools located in the field. In general it was found that the definition of a cost-studentquality education, especially in the education field, remains a challenge, especially because this discussion brings to light the complexity, tensions and contradictions of educational phenomenon in a country marked by inequality.